Formation and evolution mechanisms of truck overweight phenomenon in mainland China: Systematic and historical perspectives. (March 2023) - Jiang, Chuansheng; Hao, Chenyu; Zeng, Mingrong; Wang, Yan; Liu, Peiyi
Highlights: The contributions of all the agents (e.g. manufacturer, retailer, freight source companies, etc.) during the full life cycle of trucks are taken into account to systematically depict the cross-sectional microscopic formation mechanism of truck overweight phenomenon. the historical analysis is applied to identify the macroscopic social and economic factors behind the evolution of truck overweight phenomenon during the past over 30 years in China. Truck overweight, the seemingly personal unsafe choice of truckers, is proved to be influenced by both microscopic factors (mainly other agents during the full life cycle of trucks) and macroscopic factors (mainly the macro-economic phase and the road freight market), therefore the countermeasures should address all the main factors. Abstract: Truck overweight is an important cause of truck safety accidents, which has been persistent in the course of more than 30 years of the road freight market reform in mainland China, despite persistent efforts to stem it. In this paper, the accident causation mechanism of truck overweight is investigated based on accident cases. The cross-sectional microscopic formation mechanism of truck overweight phenomenon among truck-related agents, the longitudinal macroscopic evolution process of truck overweight phenomenon and some emerging trends in China are analyzed with the hope to fully reveal the various causes of truck overweight. Practical measures are finally proposed to steadily strengthen truck overweight control. Highlights in this paper: (1) The contributions of all the agents (e.g. manufacturer, retailer, freight source companies, etc.) during the full life cycle of trucks are taken into account to systematically depict the cross-sectional microscopic formation mechanism of truck overweight phenomenon. (2) the historical analysis is applied to identify the macroscopic social and economic factors behind the evolution of truck overweight phenomenon during the past over 30 years in China. (3) Truck overweight, the seemingly personal unsafe choice of truckers, is proved to be influenced by both microscopic factors (mainly other agents during the full life cycle of trucks) and macroscopic factors (mainly the macro-economic phase and the road freight market), therefore the countermeasures should address all the main factors.